Research of the aspects of modeling of the project management of risk of implementation system information support - Babenko, Vitalina; Nakisko, Oleksandr; Mykolenko, Inna (Technology audit and production reserves, 2017)
The object of research is the risk management of the information support system of enterprise management. One of the most problematic places is the identification of anticipated risks and their minimization. The process of risk management is associated with the complexity and duration of the implementation of the information management system of the enterprise and its relatively high cost. In the course of the study, the modeling approaches of the project risk management process were used. Stages of modeling the process of risk management of the project of implementing the information support system are determined. They include the identification and assessment of project risks, an analysis of key risks and opportunities, the definition of strategies and methods for responding to risks. As well as the development and implementation of action plans to minimize risks, measure, monitor and report on risk management activities with an analysis of the results of management decisions. For their implementation, a standard BPwin program procedure is proposed with the possibility of ABC estimation of the cost of performing each stage. Thanks to this, it is possible to control the production costs at every stage of the information support system. In comparison with similar known methods, approaches are suggested that minimize the loss of the management of enterprise management information systems as a result of the impact of risks through predictability and minimizing the risks to which the project is exposed.